MICROBIOLOGICAL ASPECT OF STAPHYLOCOCCAL INFECTION IN SEVERE DEGREE OF BURNS - Venny Tandyono (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Burns serve as one of the most common devastating forms of trauma. Significant thermal injuries induce skin disruption and immunosupression that predispose patients to infectious complication. The importance of sampling, detection, and proper treatment for wound infections will significantly increase the likelihood of clinical improvement of the patients. Case: A 44-years-old male came to hospital due to electrical shock. There were serious burns to his face, chest, arms, and legs, some of which were second- and third-degree burns. The patient was conscious, without problems on airway and breathing. Leukocytosis with neutrophilia was presented from laboratory examination, with an increase in liver enzymes and serum creatinine. The gram-positive cocci with leucocytes were revealed from gram examination, and colonization of Staphylococcus aureus was found. Intravenous cefazolin was administered according to the sensitivity test. Discussion: Infection causes the increase in morbidity and mortality of burn patients. Clinical diagnosis of infection must be supported microbiologically by gram examination and culture. One of the most common infectious agents in severe burns is Staphylococcus aureus. The significance of S.aureus as the leading cause of infection must be supported by microbiological data. Dominant growth in culture media and induction of host inflammatory response were indicated as significance of infection. Conclusion: Clinical and microbiological diagnosis of burns infection play important role to prevent complications in severe degree of burns.